DECODING BUDDHIST IMAGERY: DESCRIPTIVE ANALYSIS OF POLITICAL REPRESENTATION IN ’PAPILIO BUDDHA’ AND ’MADRAS’ - S., Sumithra; R., Subramani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Buddhism, a religion and philosophy founded by Gautama Siddhartha, (Buddha) around 2,500 years ago, has been utilized as a counter-hegemonic force to challenge dominant socio-political structures in India. By embracing Buddhism, individuals and communities can resist and subvert the oppressive structures and ideologies that have been used to marginalize and exclude them. This research analyzes how the films "Papilio Buddha" (2013) and "Madras" (2014), deploy Buddhist themes and motifs to critique socio-political issues, particularly Dalit struggle, resistance against caste oppression and Rights. The objectives of this research are to investigate how Buddhist symbols and imagery address social and political issues and to explore the significance of Buddhism in forming political identities and promoting collective resistance. Furthermore, this research examines the political symbolism of Buddhism in the films "Papilio Buddha" and "Madras", Through the insights of B.R. Ambedkar who argued that Buddhism has emerged as a counter–hegemonic force to the oppressive Brahmanical system, perpetuating inequality and social injustice by applying Saussurean semiotics and structuralism theory to interpret the deliberate application of Buddhist symbolism in these stories, highlighting the power of film as a medium for political discourse.